The National Association of Veterans and Friends of Indochina: Commemoration of the Indochina War and the "positive" role of colonialism - Edwards, M. Kathryn (Hagar: Studies in Society and Culture, 2010)
From the brutal repression of the demonstrations by colonial soldiers in Sétif in 1945 to the wars of decolonization in Indochina and Algeria, the French have experienced considerable difficulty in both reconciling themselves with their colonial past and incorporating it into the national narrative. To illustrate these issues, this study focuses on the National Association of Friends and Veterans of Indochina (ANAI), a group mandated to promote awareness of the Indochina War and a positive interpretation of the colonial project. The examination of its internal commemorative activities, its role in lobbying for greater state-sponsored commemoration and its commitment to promoting the positive aspects of colonialism reveals the process of constructing and promoting particular narratives of the war and the colonial period. In broader terms, this case study illustrates the processes by which special interest groups impact official and public discourses.